2020
DOI: 10.1038/s41598-020-76704-z
|View full text |Cite
|
Sign up to set email alerts
|

No relationship between the acromiohumeral distance and pain in adults with subacromial pain syndrome: a systematic review and meta-analysis

Abstract: To determine whether subacromial space (i.e. acromiohumeral distance; AHD, and/or occupation ratio percentage) differs between people with subacromial pain syndrome (SAPS) and those without. To investigate whether there is a correlation between subacromial space and pain or disability in adults with SAPS and whether temporal changes in pain or disability are accompanied by changes in subacromial space. Systematic review and meta-analysis. Fifteen studies with a total of 775 participants were included. Twelve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 77 publications
(181 reference statements)
1
17
1
Order By: Relevance
“…Petersson and Redlund-Johnell [10] and Jost et al [8] stated that an acromiohumeral distance of ≤ 7 mm measured on anteroposterior radiographs triggered significant damage to the rotator cuff muscles and reduced the likelihood of successful surgery. Park et al [38] found a significant difference between VAS and subacromial distance values in the study they conducted in the general population aged 29-74 whose pain persisted for > 3 months. In our study, similar to the literature, 7 mm was set as the critical value for the subacromial distance and identified the changes above and below this threshold.…”
Section: Discussionmentioning
confidence: 90%
“…Petersson and Redlund-Johnell [10] and Jost et al [8] stated that an acromiohumeral distance of ≤ 7 mm measured on anteroposterior radiographs triggered significant damage to the rotator cuff muscles and reduced the likelihood of successful surgery. Park et al [38] found a significant difference between VAS and subacromial distance values in the study they conducted in the general population aged 29-74 whose pain persisted for > 3 months. In our study, similar to the literature, 7 mm was set as the critical value for the subacromial distance and identified the changes above and below this threshold.…”
Section: Discussionmentioning
confidence: 90%
“…As previously mentioned, treatment of a patient with subacromial pain syndrome should not only focus on addressing a possible decrease in the AHD, but also on the importance of other biopsychosocial factors ( Park et al, 2020 ). Nevertheless, according to the authors the evidence is still limited to determine the correlation between AHD and pain or disability, as the included studies had different outcome measures and different study population ( Park et al, 2020 ). The differences in the AHD found in our study justify the use of this technique to obtain an increase in the distance in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is the first approach to the subacromial pain syndrome, with shoulder taping as one of the most used techniques ( Zanella et al, 2001 ; Cools et al, 2002 ; Selkowitz et al, 2007 ; Thelen, Dauber & Stoneman, 2008 ). A recent review has studied the relationship between the AHD and the existence of symptoms such as pain and disability, suggesting the importance of also addressing other biopsychosocial factors when dealing with a symptomatic patient ( Park et al, 2020 ). There are many different studies where taping is applied to modify shoulder articular properties ( i.e., shoulder’s kinematics, muscle force, range of motion, neuromuscular control, pain or joint stability) ( Host, 1995 ; Ackermann, Adams & Marshall, 2002 ; Lewis, Wright & Green, 2005 ; Thelen, Dauber & Stoneman, 2008 ; Shaheen et al, 2013 ; Harput et al, 2017 ), some of them also demonstrating the effectiveness of the taping to increase the AHD ( Luque-Suarez et al, 2013 ; Lyman et al, 2017 ; Bdaiwi et al, 2017 ; Harput et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main factor in the development of a swimmer's shoulder seems to be the high training volume during growth in the absence of a balanced dryland training program (Porter et al, 2020). Most swimming strokes consist of a pull-through phase that generates speed and a recovery phase where the arm is over the water (Bak, 2010).…”
Section: Introductionmentioning
confidence: 99%